2021
DOI: 10.1111/bjh.17521
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of droplet digital polymerase chain reaction for measuring BCR‐ABL1 in chronic myeloid leukaemia in an international interlaboratory study

Abstract: Summary Measurement of BCR activator of RhoGEF and GTPase ‐ABL proto‐oncogene 1, non‐receptor tyrosine kinase (BCR‐ABL1) mRNA levels by reverse transcription quantitative polymerase chain reaction (RTqPCR) has been critical to treatment protocols and clinical trials in chronic myeloid leukaemia; however, interlaboratory variation remains a significant issue. Reverse transcriptase droplet digital PCR (RTddPCR) has shown potential to improve testing but a large‐scale interlaboratory study is required to definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…We note a recent study demonstrated similar sensitivity between optimised RT-qPCR as compared with ddPCR under standardised conditions. 13 In contrast, we demonstrated an increased assay sensitivity with ddPCR, using increased complementary DNA input and number of reactions performed. Our results have similar clinical implications to previous reports, 7,8 in particular Nicolini et al, 14 who showed a BCR::ABL1 of <0.0023% correlated with TFR success.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 88%
“…We note a recent study demonstrated similar sensitivity between optimised RT-qPCR as compared with ddPCR under standardised conditions. 13 In contrast, we demonstrated an increased assay sensitivity with ddPCR, using increased complementary DNA input and number of reactions performed. Our results have similar clinical implications to previous reports, 7,8 in particular Nicolini et al, 14 who showed a BCR::ABL1 of <0.0023% correlated with TFR success.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 88%
“…In this study performance between sites and operators showed low variability in ddPCR, a challenge for many qPCR-based assays, yet essential for long term monitoring. A study used 10 BCR :: ABL1 positive samples across 11 labs, showed higher inter-lab CV% in RTq-PCR when compared head-to-head with RTddPCR [ 35 ]. The sum of these performance characteristics led to FDA regulatory clearance.…”
Section: Discussionmentioning
confidence: 99%
“…These include, 1) measuring actual molecules (positive droplets) rather than estimating starting template amount by amplification slope and standard curve samples; 2) insensitivity to sample inhibition due to the use of endpoint counting and droplet chemistry rather than amplification slope, the latter easily influenced by poor quality template and/or endogenous and exogenous interferents that might inhibit amplification, and 3) sampling a large number of droplets, which increases the precision of the assay and can increase the sensitivity of the assay. These characteristics also add robustness to the assay performance and allow high levels of reproducible results lab to lab, operator to operator, lot to lot, and even assay to assay [ 22 , 35 , 39 – 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to use ddPCR, a technique which is relatively insensitive to differences in amplification efficiency as well as having other advantages such as producing results that are less variable that those produced by RT-qPCR and the lack of requirement for a standard curve [ 34 37 ]. Our initial data using control materials indicated that ddPCR results do not show the transcript-related differences that were seen using RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%